1975
DOI: 10.1017/s0022029900015211
|View full text |Cite
|
Sign up to set email alerts
|

Autoxidation in milk rich in linoleic acid I. An objective method for measuring autoxidation and evaluating antioxidants

Abstract: Autoxidation was studied in milk obtained from cows fed on formaldehyde-treated casein-safflower oil supplement. The fat of this milk contained high levels of linoleic acid. A rapid disappearance of dissolved oxygen (DO), measured by using an oxygen electrode, from milk samples stored at 0 °C in tubes without headspace, coincided with the development of oxidized flavours detected organoleptically. A correlation coefficient of 0-9 with 69 degrees of freedom (P < 0-001) was obtained between the amount of DO disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…The consistent and highly significant increase in concentrations of PUFA in milk from cows fed RCS provides an explanation for the reduced oxidative stability of milk. Many earlier studies have shown that increasing concentrations of unsaturated fatty acids in milk, particularly of PUFA C 18:2 and C 18:3 , will increase the susceptibility of milk to oxidation (e.g., Sidhu et al, 1975;Granelli et al, 1998;Timmons et al, 2001).…”
Section: Oxidative Stability Of Milkmentioning
confidence: 99%
“…The consistent and highly significant increase in concentrations of PUFA in milk from cows fed RCS provides an explanation for the reduced oxidative stability of milk. Many earlier studies have shown that increasing concentrations of unsaturated fatty acids in milk, particularly of PUFA C 18:2 and C 18:3 , will increase the susceptibility of milk to oxidation (e.g., Sidhu et al, 1975;Granelli et al, 1998;Timmons et al, 2001).…”
Section: Oxidative Stability Of Milkmentioning
confidence: 99%
“…A potential downside of such a breeding strategy is that unsaturated milk FA are more prone to oxidize (Sidhu et al, 1975;Barrefors et al, 1995;Granelli et al, 1998;Timmons et al, 2001), giving a carbon, metal, talcum, or fishy flavor to the milk (Shipe et al, 1978). This off-flavor results from volatile compounds that accumulate in the milk through the oxidation of the double bonds between the carbon atoms in unsatu-4611 rated FA.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the susceptibility of milk to develop SOF increases with elevated concentration of long chain unsaturated milk fatty acids (Sidhu et al 1975; Granelli et al 1998; Timmons et al 2001). However, because intake of polyunsaturated fatty acids (PUFA) have been associated with improved blood cholesterol profile in humans significant efforts have been made during the last decade to increase PUFA in cow's milk fat.…”
mentioning
confidence: 99%